Enxaguatórios bucais a base de ervas – efeito no biofilme dental, inflamação gengival e halitose: revisão sistemática - Santi, Samantha Simoni (2018)
Mouthrinses have been used as adjuncts to oral hygiene in an attempt to optimize the control of dental biofilm, gingival inflammation and halitosis. In this context, herbal terapy, with products based on herbs and plants, have been gaining greater market acceptance. The present dissertation proposed to systematically review randomized clinical trials that evaluated the effect of herbal products as adjunct to oral hygiene. Two systematic reviews were made on dental biofilm, gingival inflammation (RS1) and halitosis (RS2) outcomes. The search was conducted in PubMed/MEDLINE, Cochrane - Central Register of Controlled Trials (CENTRAL), EMBASE, Web of Science, LILACS, Clinical Trials register, PROSPERO, The National Dutch Trial Register, EU clinical trials register, NARCIS and Gray literature (opengrey, thesis bank of capes) databases until April 3, 2018. No language restriction was performed. In the analysis with dental plaque and gingival inflammation outcomes, 23 studies were included and with halitosis outcome, 4 studies were included. Due to the high heterogeneity observed in the characteristics in both studies, no meta-analysis was performed. As a general result, herbal mouthrinses showed a significant reduction in dental dental plaque, gingival inflammation and halitosis when compared to placebo solutions. In the outcome of biofilm and gingival inflammation as well as some herbs Camelia sinensis, Azadirachta indica, Anacardium occidentale Linn, Schinus terebinthifolius e Curcuma longa results found for chlorhexidine. In the halitosis, only one study compared the herbal product (Sesamum indicum) with chlorhexidine, presenting significantly better results for the herbal product in the self-reported method. However, the studies included in both reviews presented, for the most part, a moderate risk of bias, which limits the internal validity of the conclusions. Thus, there is still a lack of evidence with less risk of bias and more clearly indicating the magnitude of the effect of herbal mouthrinse for its recommendation.